2019
DOI: 10.3389/fmars.2019.00645
|View full text |Cite
|
Sign up to set email alerts
|

Whistle Classification of Sympatric False Killer Whale Populations in Hawaiian Waters Yields Low Accuracy Rates

Abstract: Cetaceans are ecologically important marine predators, and designating individuals to distinct populations can be challenging. Passive acoustic monitoring provides an approach to classify cetaceans to populations using their vocalizations. In the Hawaiian Archipelago, three genetically distinct, sympatric false killer whale (Pseudorca crassidens) populations coexist: a broadly distributed pelagic population and two islandassociated populations, an endangered main Hawaiian Islands (MHI) population and a Northwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…(Cranford 1999;MacLeod and MacLeod 2009;Ralls and Mesnick 2009;MacLeod 2010;Goldbogen et al 2019). A known trend is that the larger the animal, the louder sound it will produce (Ralls and (Murray et al 1998) and differences in vocalization were recorded between populations but not between sexes (Rendell et al 1999;Oswald et al 2003;Sanino and Fowle 2006;Barkley et al 2019). The allometric parallel slopes observed for males and females showed that the directions of shape changes in the cranium are conserved among sexes.…”
Section: Sexual Size Dimorphismmentioning
confidence: 99%
“…(Cranford 1999;MacLeod and MacLeod 2009;Ralls and Mesnick 2009;MacLeod 2010;Goldbogen et al 2019). A known trend is that the larger the animal, the louder sound it will produce (Ralls and (Murray et al 1998) and differences in vocalization were recorded between populations but not between sexes (Rendell et al 1999;Oswald et al 2003;Sanino and Fowle 2006;Barkley et al 2019). The allometric parallel slopes observed for males and females showed that the directions of shape changes in the cranium are conserved among sexes.…”
Section: Sexual Size Dimorphismmentioning
confidence: 99%
“…An analysis of Pearson's correlation coefficients revealed high linear correlation between delta frequency and high frequency (ρ = 0.94). Because previous studies have shown the inclusion of highly correlated variables impacts variable importance weightings in the model (Gregorutti et al, 2017;Barkley et al, 2019), we removed variables from the RFA if the Pearson's correlation coefficient exceeded ±0.8 as recommended by Barkley et al (2019). We used the Cohen's Kappa statistic (Landis & Koch 1977) to evaluate the model performance (Cohen, 1960) which measures the strength of agreement as follows; 0.01-0.20 slight, 0.21-0.40 fair, 0.41-0.60 moderate, 0.61-0.80 substantial, and 0.81-100 nearly perfect.…”
Section: Characterization Of the Soundscapementioning
confidence: 99%
“…The amplitude part of the measurements for the targets and clutter is simulated by randomly drawing from the pdfs in Eqs. ( 11) and (10), respectively, with k ¼ 3:7 and the expected target SNR bounds ½d 1 ; d 2 ¼ ½5; 20 dB.…”
Section: Simulationsmentioning
confidence: 99%
“…The clutter amplitude was simulated by randomly drawing from the pdf in Eq. (10), where k ¼ 3:7. The GM-PHD-SA tracking results showed that while the subgroup was tracked when only measurements from either whistles and (to some extent) clicks were available, better results were achieved when both measurements were combined (Fig.…”
Section: Filtermentioning
confidence: 99%
See 1 more Smart Citation